ChemInform Abstract: A Combined Computational and Experimental Investigation of the Oxidative Ring‐Opening of Cyclic Ethers by Oxoammonium Cations. Issue 33 (27th July 2016) - Loman, Jacob. J.; Carnaghan, Emma R.; Hamlin, Trevor A.; Ovian, John M.; Kelly, Christopher B.; Mercadante, Michael A.; Leadbeater, Nicholas E.
Abstract: The limited substrate scope of the title reaction with regard to the ethers′ ring size and aryl substituents is evidenced by elucidation of the reaction mechanism by DFT calculations.